CHLOROPHYLL METER: A TOOL FOR ASSESSING DYNAMIC NITROGEN SUPPLY IN POTATO CROP UNDER ORGANIC VIS-Ã€-VIS INORGANIC NUTRIENT MANAGEMENT OPTIONS - Shukla, Arvind K.; Khan, M. A; Upadhayay, N C; Singh, B. P; Lal, S. S; Pandey, S K (Potato Journal, 2013)
In order to optimize tuber yield in organic potato production systems, knowledge of crop growth in relation to N limitation is necessary. The SPAD Chlorophyll meter reading appears promising for rapid, on farm analysis of crop nitrogen status. Chlorophyll meter readings (using a Minolta SPAD-502 chlorophyll meter) and leaf N content were recorded during the growing season (from 28 to 70 DAS at 1012 days interval) in existing experiments to assess the N status of potato crop. Highly significant linear and quadratic trends were obtained for the regression of leaf N content (R2 = 0.59 to 0.83) and tuber yields (R2 = 0.43 to 0.65) and chlorophyll meter readings. SPAD readings decreased as plants aged.